2013
DOI: 10.1161/atvbaha.113.301607
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Prothrombin Promotes Venous, but Not Arterial, Thrombosis in Mice

Abstract: Objective Individuals with elevated prothrombin, including those with the prothrombin G20210A mutation, have increased risk of venous thrombosis. Although these individuals do not have increased circulating prothrombotic biomarkers, their plasma demonstrates increased tissue factor-dependent thrombin generation in vitro. The objectives of this study were to determine the pathologic role of elevated prothrombin in venous and arterial thrombosis in vivo, and distinguish thrombogenic mechanisms in these vessels. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
45
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 43 publications
(49 citation statements)
references
References 51 publications
4
45
0
Order By: Relevance
“…[38][39][40][41][42][43] It is tempting to speculate that these dense networks trap more RBCs, resulting in large, occlusive venous thrombi. Indeed, we previously observed that hyperprothrombinemia leads to the formation of clots with increased network density 44 and that mice with elevated prothrombin produce significantly larger venous thrombi 38 that have higher RBC content (M. M. Aleman and A.S.W., unpublished observations, October 31, 2012). Together, these findings suggest an abnormally high density of crosslinked fibrin promotes venous occlusion by increasing RBC retention in the thrombus, and therefore, thrombus size.…”
Section: Discussionmentioning
confidence: 99%
“…[38][39][40][41][42][43] It is tempting to speculate that these dense networks trap more RBCs, resulting in large, occlusive venous thrombi. Indeed, we previously observed that hyperprothrombinemia leads to the formation of clots with increased network density 44 and that mice with elevated prothrombin produce significantly larger venous thrombi 38 that have higher RBC content (M. M. Aleman and A.S.W., unpublished observations, October 31, 2012). Together, these findings suggest an abnormally high density of crosslinked fibrin promotes venous occlusion by increasing RBC retention in the thrombus, and therefore, thrombus size.…”
Section: Discussionmentioning
confidence: 99%
“…+/+ mice as described (58,59). Briefly, anesthetized mice were subject to sterile laparotomy and exposure of the IVC.…”
Section: and F13amentioning
confidence: 99%
“…1 Artificially increasing the plasma prothrombin concentration does not increase total platelet accumulation in an arterial injury model, 18 suggesting that increasing the concentration of thrombin precursor does not lead to increased thrombin production or increased platelet recruitment. Finally, our model predicts that changing the dynamics of transport changes the effective concentration of agonists and thus thrombus architecture.…”
mentioning
confidence: 99%